2021
DOI: 10.1080/22221751.2021.1899772
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological characteristics of enterovirus infection before and after the use of enterovirus 71 inactivated vaccine in Kunming, China

Abstract: Enterovirus A71 (EV-A71) inactivated vaccines have been widely inoculated among children in Kunming City after it was approved. However, there was a large-scale outbreak of Enteroviruses (EVs) infection in Kunming, 2018.The epidemiological characteristics of HFMD and EVs were analyzed during 2008 to 2018, which are before and three years after EV-A71 vaccine starting to use. The changes of infection spectrum were also investigated, especially for severe HFMD in 2018.The incidence of EV-A71 decreased dramatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 32 publications
1
37
1
Order By: Relevance
“…The introduction of the EV-A71 immunisation in 2016 resulted in a significant decrease in both the number of patients with EV-A71-related HFMD and severe cases, demonstrating the favourable effect of the vaccination campaign. A longitudinal surveillance study conducted in Chengdu, a big city in southwest China, revealed the initial evidence for the effectiveness of the programmatic vaccination against EV71, in line with subsequent studies in some other regions [5, 17, 18]. Except for the decline of the EV71 prevalence, the pathogen spectrum associated with HFMD were also altered as reported in these studies.…”
Section: Discussionsupporting
confidence: 71%
“…The introduction of the EV-A71 immunisation in 2016 resulted in a significant decrease in both the number of patients with EV-A71-related HFMD and severe cases, demonstrating the favourable effect of the vaccination campaign. A longitudinal surveillance study conducted in Chengdu, a big city in southwest China, revealed the initial evidence for the effectiveness of the programmatic vaccination against EV71, in line with subsequent studies in some other regions [5, 17, 18]. Except for the decline of the EV71 prevalence, the pathogen spectrum associated with HFMD were also altered as reported in these studies.…”
Section: Discussionsupporting
confidence: 71%
“… 6 , 8 This finding prompted concerns about whether the epidemiology of HFMD will change due to vaccination and whether there might be a shift in serotypes. A few local studies 9 , 10 , 11 , 12 have been conducted to address EV-A71 vaccination impacts, but the evidence generated has been limited. Among the four studies conducted, only periodicity − without risk factor analysis − has been described.…”
Section: Introductionmentioning
confidence: 99%
“…Many EVs, including echoviruses, cocirculated in both sporadic and epidemic cases of HFMD 14 18 . Since the introduction of an inactivated EV-A71 vaccine, the prevalent etiological agents of HFMD have changed, and CV-A6 has become the main pathogen in mainland China 24 , 25 . EVs, and especially echoviruses, are the major agents of aseptic meningitis 3 5 , and EV-B, including echoviruses, can also cause HFMD 18 20 .…”
Section: Discussionmentioning
confidence: 99%